A tree well travelled: global genetic structure of the invasive tree Acacia saligna. (21st November 2014) - Thompson, Genevieve D.; Bellstedt, Dirk U.; Richardson, David M.; Wilson, John R. U.; Le Roux, Johannes J.; Richardson, James
Abstract Aim Invasiveness of an introduced species in one region is often used to predict risk and inform management of the same species elsewhere. This assumes that entities in both regions are equivalent in their ecology and response to management. However, intraspecific genetic variation can result in differences in performance between regions. We conducted population genetic and phylogeographic analyses of the widely introduced and intraspecifically diverse Australian tree species Acacia saligna, in order to improve our understanding of its worldwide invasion history. Location The native range of A. saligna in Western Australia and introduced ranges in eastern Australia, Israel, Italy, New Zealand, Portugal, South Africa, Spain and the USA. Methods We analysed microsatellite genotype data obtained from 447 individuals of A. saligna (including reference populations of known subspecies lineages) using Bayesian assignment analysis. We also reconstructed parsimony networks and a phylogeny using data from the nuclear external transcribed spacer (ETS) gene region for a subset of 120 individuals. Results There was no consistent genetic pattern in introduced populations in different parts of the world. All three subspecies lineages of A. saligna have been moved around the world, showing high levels of admixture in some introduced populations. A previously identified novel and cultivated South African lineage was also identified in Portugal and Italy. Main conclusions With different subspecies lineages present in different regions globally, it is unclear exactly how effective management approaches of invasions in one region will be in other regions. For example, the successful biological control agents against cultivated lineages of A. saligna in South Africa will probably be effective against similar genotypes in Portugal but not against dissimilar lineages present elsewhere. Further work is needed to conclusively link the relative extent of invasions to genetic differences, and to determine whether genetic novelty can explain the widespread invasions of A. saligna observed in South Africa and Portugal.